Xây dựng tiêu chí đánh giá năng lực dạy học STEM của giáo viên phổ thông tại Việt Nam - Lê, Thị Thu Hiền; Phạm, Kim Chung; Lê, Chí Nguyện; Vũ, Thị Thuý; Nguyễ, Thị Lan Ngọc (Tạp chí Giáo dục, 2024)
STEM education (Science, Technology, Engineering, and Mathematics) is a teaching approach that countries around the world are focusing on in the context of the Fourth Industrial Revolution. The 2018 general education program incorporated STEM education as a new educational approach aimed at developing learners’ competencies, helping to implement the roadmap for training high-quality human resources to meet Vietnam’s international integration requirements. Starting from the 2020-2021 academic year, the Ministry of Education and Training has mandated the implementation of STEM education in all secondary schools in Vietnam. This presents many challenges for secondary schools, particularly in assessing the STEM teaching competency of general education teachers to meet the required standards and ensure effective STEM teaching. This article discusses the assessment of teaching competency, STEM teaching competency of secondary school teachers, and the criteria for evaluating the STEM teaching competency of general education teachers in Vietnam.